2019
DOI: 10.1002/jcp.29262
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA TPT1‐AS1 downregulates the microRNA‐770‐5p expression to inhibit glioma cell autophagy and promote proliferation through STMN1 upregulation

Abstract: Through the microarray analysis, long noncoding RNA TPT1-AS1 (TPT1-AS1) was identified in the development of glioma. However, the specific effect of TPT1-AS1 on glioma autophagy in the recent years has not fully been investigated. Therefore, the purpose of our present study is to investigate the function of TPT1-AS1 on affecting autophagy of glioma cells through regulation of microRNA-770-5p (miR-770-5p)-mediated How to cite this article: Jia L, Song Y, Mu L, et al. Long noncoding RNA TPT1-AS1 downregulates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 28 publications
4
10
0
Order By: Relevance
“…However, in contrast to our findings, TPT1-AS1 was determined as a tumor suppressor in gliomas in a recent study. The authors identified that TPT1-AS1 inhibited glioma cell autophagy and proliferation by sponging miR-770-5p [19][20][21]. In accordance with our study, another report showed that TPT1-AS1 promoted tumorigenesis and metastasis of ovarian cancer by inducing TPT1 expression [22], which also identified TPT1-AS1 as an oncogenic factor.…”
Section: Agingsupporting
confidence: 90%
“…However, in contrast to our findings, TPT1-AS1 was determined as a tumor suppressor in gliomas in a recent study. The authors identified that TPT1-AS1 inhibited glioma cell autophagy and proliferation by sponging miR-770-5p [19][20][21]. In accordance with our study, another report showed that TPT1-AS1 promoted tumorigenesis and metastasis of ovarian cancer by inducing TPT1 expression [22], which also identified TPT1-AS1 as an oncogenic factor.…”
Section: Agingsupporting
confidence: 90%
“…An increasing number of studies has demonstrated that miR-574-5p can be sponged by lncRNA, like lncRNA PTCSC3 and lncRNA MFI2-AS1, to modulate growth and metastasis of cancer cells [36,37]. In addition, miR-770-5p has been found to be downregulated by lncRNA TPT1-AS1 and correspondingly upregulated the expression of STMN1, leading to promotion of the proliferation of Glioma cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-oncogene AC016405.3 restrained GBM cell proliferation and migration by sponging miR-19a through regulation of ten-eleven translocation-2 (TET2) (28). LncRNA TPT1-AS1 inhibited glioma cell autophagy by decreasing the expression of miR-110-5p, and upregulating STMN1 expression promoted the proliferation of glioma cells (29). In addition, mRNAs can indirectly regulate gene phenotypes by signaling pathways via the post-transcriptional regulation of ceRNAs.…”
Section: The Functions and Mechanisms Of Lncrnas In Gliomasmentioning
confidence: 99%